Effect of Activity-Based Method on Students’ Academic Performance in Basic Science - Green, Balafama (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2024)
The study investigated the effect of the activity-based method on the academic performance of students in Basic Science. Using a quasi-experimental design with a pre-test-post-test control group setup, the study involved 87 Junior Secondary School two (JSSII) Basic Science students from two co-educational schools in Port Harcourt City Local Government Area, Rivers State, Nigeria, selected purposively. The data collection instrument was the Achievement Test in Basic Science (ATBS), which demonstrated a reliability coefficient of 0.76 through a test-re-test technique. Data analysis employed Analysis of Covariance (ANCOVA). The results revealed a significant difference in the academic achievement of students exposed to activity-based methods compared to those taught using expository techniques. Notably, students in the activity-based method group outperformed their counterparts in the expository technique group. Additionally, gender did not exert a significant influence on students' academic achievement in Basic Science. Based on these findings, recommendations include advocating for the government's provision of well-equipped and functional laboratories conducive to implementing activity-based methods, thereby enhancing students' academic performance in basic science.